PENGARUH KOMPENSASI, LINGKUNGAN KERJA, KEPEMIMPINAN, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR DINAS KESEHATAN KABUPATEN PONOROGO - Baskoro, Yesi Daniel Tri; Suddin, Alwi; Sutarno, Sutarno (Universitas Slamet Riyadi, 2019)
The purpose of this study was to analyze the significance of the influence of the influence of workplace leadership and work discipline compensation on the performance of the Ponorogo district health office employee data collection in the form of questionnaire answers as primary data and documentation as secondary data. The number of research samples as many as 74 employees with the sampling method using saturated sampling. The data analysis method used is the validity and reliability test, the classic assumption test, the hypothesis test, the F test, and the coefficient of determination test. The regression calculation results show that the work environment and work discipline have a significant effect on the performance of the employees of the district health office in Ponorogo. This is indicated by the significant probability value of each variable < 0,05. While compensation and leadership have insignificant effect on the performance of employees of the Ponorogo district health office. This is indicated by the significant probability value > 0,05.